Peripheral ameloblastoma: case report and our experience 20 years - Luciani, Fabio; Papa, Edoarto; Leggeri, Andrea; Condò, Roberta; Giovannetti, Filippo; Calabrese, Leonardo (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: The purpose of this study was to determine the clinical and histological features and treatment of peripheral ameloblastoma. Peripheral Ameloblastoma is a rare benign odontogenic tumor that concerns soft tissue and have a typical extraosseous localization.Methods: Aim of this work is to show its clinical and histological characters, in order to define some useful information for differential diagnosis with other oral neoformations, comparing literature with our data, collected in ten years of clinical activity of Oral and Maxillofacial Surgery Unit of Policlinico Tor Vergata in Rome.Results: Prognosis of PA is certainly favourable, with a restitutio ad integrum close to 100%. In the period between October 2011 and November 2021, we reported 8 diagnoses of P.A. Medium age of the group with diagnosis of PA was 71,4 y with a SD: 3,65. P.A.’s incidence in our sample of patients was 0,26%.Conclusions: PA is a benign odontogenic tumor that requires a careful diagnosis, a complete surgical eradication and adequate follow up, because malignant evolution is rare but possible.